ATP promotes immunosuppressive capacities of mesenchymal stromal cells by enhancing the expression of indoleamine dioxygenase. Issue 4 (10th October 2018) - Lotfi, Ramin; Steppe, Lena; Hang, Regina; Rojewski, Markus; Massold, Marina; Jahrsdörfer, Bernd; Schrezenmeier, Hubert
Abstract: Introduction: MSCs are often found within tumors, promote cancer progression and enhance metastasis. MSCs can act as immuosuppressive cells, partially due to the expression of the enzyme indoleamine dioxygenase (IDO) which converts tryptophan to kynurenine. Decreased concentration of tryptophan and increased kynurenine, both interfere with effective immune response. Damage associated molecular patterns (DAMPs) including ATP are found within the tumor microenvironment, attract MSCs, and influence their biology. Methods: Bone marrow derived MSCs were exposed to ATP for 4 days, in the presence of 100 ng IFNγ/mL. Intracellular expression of IDO in MSCs was assessed by FACS. Conditioned media from thus stimulated MSCs was analyzed for kynurenine content and its suppressive effect on lymphocyte proliferation. Apyrase or P2 × 7‐receptor antagonist (AZ 11645373) were applied in order to inhibit ATP induced effect on MSCs. Results: We demonstrate, that ATP at concentrations between 0.062 and 0.5 mM increases dose dependently the expression of IDO in MSCs with subsequent increased kynurenine concentrations within the supernatant at about 60%. This effect could be abolished completely in the presence of ATP degrading enzyme (apyrase) or when MSCs were pretreated with a P2 × 7‐receptor antagonist (AZ 11645373). Consistently, supernatants from MSCs stimulated with ATP, inhibited lymphocyte proliferation from 65% to 16%. Conclusions: We characterized ATP as a DAMP family member responsible for necrosis‐induced immunomodulation. Given the increased concentration of DAMPs within tumor tissue and the fact that DAMPs can act as chemotattractants to MSCs, our results have implications for therapeutic strategies targeting the tumor microenvironment. Abstract : ATP is released from necrotic (Tumor) cells and enhance expression of IDO in mesenchymal stromal cells (MSCs) if inflammatory cytokines like IFNg are present. IDO promotes production of kynurenie by MSCs and thus supports immunosuppression within tumor tissue.